2020
DOI: 10.1080/21688370.2020.1804249
|View full text |Cite
|
Sign up to set email alerts
|

IL-1β strengthens the physical barrier in gingival epithelial cells

Abstract: Periodontitis is one of the most common oral diseases worldwide and is caused by a variety of interactions between oral bacteria and the host. Here, pathogens induce inflammatory host responses that cause the secretion of proinflammatory cytokines such as IL-1β, IL-6, and IL-8 by oral epithelial cells. In various systems, it has been shown that inflammation compromises physical barriers, which enables bacteria to invade the tissue. In this study, we investigated the barrier properties of the oral mucosa under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…The oral mucosa provides a primary physical barrier, which is achieved by a high degree of differentiation and cell-cell linkages of the epithelial cells, known as tight junctions (TJ). Studies on oral epithelia have shown that pro-inflammatory cytokines can alter the physical barrier, such as specific expression of TJ proteins [ 27 ]. Moreover, alterations of the epithelial barrier with disturbances in desmosomes, adherens and tight junctions in OLP have been reported [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The oral mucosa provides a primary physical barrier, which is achieved by a high degree of differentiation and cell-cell linkages of the epithelial cells, known as tight junctions (TJ). Studies on oral epithelia have shown that pro-inflammatory cytokines can alter the physical barrier, such as specific expression of TJ proteins [ 27 ]. Moreover, alterations of the epithelial barrier with disturbances in desmosomes, adherens and tight junctions in OLP have been reported [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…For cell culture experiments, hTERT-immortalized human gingival keratinocytes (OKG4/bmi1/TERT) kindly provided by Susan Gibbs were used. Primary gingival epithelial cells (GECs) and fibroblasts (GF) were dissected from oral mucosal tissues, obtained from oral and periodontal surgery in the Department of Periodontology, Oral Medicine, and Oral Surgery (Charité – Universitätsmedizin Berlin), and it was approved by the institutional review board (EA/185/16). Epithelial cells were cultured and differentiated with the same media and reagents as described by our group . For the 3D mucosa organoids, fibroblasts (immortalized, IhGF; primary human, GF) were co-cultured with OKG4 or primary GECs, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Gene expression of the cytokines TNFα, IL-1β, IL-6, and IL-8 was determined and normalized to the housekeeping gene GAPDH. Relative gene expression was determined via the delta–delta Ct method . The primers were purchased from Metabion GmbH (Planegg/Steinkirchen, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…Salivary gland function and saliva composition is rapidly altered in response to cancer therapies and impairs the ability to retain optimal conditions to balance microbial and epithelial interactions, including compositional shifts in the oral microbiome [31]. Epithelial cells lining the oral cavity express a range of innate immune sensors that mediate signals between microbes and immune cells [32] and have been shown to be major contributors of IL-1β secretion during oral inflammation [33]. IL-1β has attracted major attention in OM research due to its diverse role in injury development and inflammatory signals [34,35].…”
Section: The Innate Immune System In Om Developmentmentioning
confidence: 99%